Trinitas Visional: Trio Surgawi Ellen G. White dan Adventisme Kontemporer - Deky Hidnas Yan Nggadas; Meriwati Meriwati (STT Pelita Dunia, 2025)
Ellen G. White is highly esteemed in Adventism as an infallible interpreter of Scripture. She is also famous for a concept she referred to as the